1989
DOI: 10.1177/0011128789035001002
|View full text |Cite
|
Sign up to set email alerts
|

Girls' Crime and Woman's Place: Toward a Feminist Model of Female Delinquency

Abstract: This article argues that existing delinquency theories are fundamentally inadequate to the task of explaining female delinquency and official reactions to girls' deviance. To establish this, the article first reviews the degree of the androcentric bias in the major theories of delinquent behavior. Then the need for a feminist model of female delinquency is explored by reviewing the available evidence on girls' offending. This review shows that the extensive focus on disadvantaged males in public settings has m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
256
1
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 448 publications
(270 citation statements)
references
References 27 publications
5
256
1
8
Order By: Relevance
“…Self-report studies have shown that youths who commit crimes are more likely to be victims of crime committed against them (Wikstrom & Butterworth, 2006), which is in line with our results. Although it is well established that female victimization and peer pressure are two important risk factors for understanding female delinquent behavior (Chesney-Lind, 1989;Giordano, Longmore & Manning, 2006), portraying adolescent female offenders as sole victims of deviant peers and romantic partners, or describing their delinquent behavior as a direct cause of their victimization, is to oversimplify a more complicated process.…”
Section: Discussionmentioning
confidence: 99%
“…Self-report studies have shown that youths who commit crimes are more likely to be victims of crime committed against them (Wikstrom & Butterworth, 2006), which is in line with our results. Although it is well established that female victimization and peer pressure are two important risk factors for understanding female delinquent behavior (Chesney-Lind, 1989;Giordano, Longmore & Manning, 2006), portraying adolescent female offenders as sole victims of deviant peers and romantic partners, or describing their delinquent behavior as a direct cause of their victimization, is to oversimplify a more complicated process.…”
Section: Discussionmentioning
confidence: 99%
“…For girls in particular, there is reason to believe that unique factors are associated with violence and delinquency (e.g. sexual abuse and victimization in the home, Chesney-Lind, 1989attachment and social bonds, Gilligan & Wiggins, 1988), introducing the possibility that variables other than those assessed under the rubric of psychopathy serve as more effective markers of risk in girls. Studies that assess the relative power of these variables versus psychopathic features over time in predicting violence are required to determine whether these factors contribute independently or interactively to outcomes, or whether one plays a more stable and central role.…”
Section: Discussionmentioning
confidence: 99%
“…Estudios en el tema (Carlen & Worrall, 2004;Chesney-Lind, 1989;Larrauri, 1994) indican que las mujeres que transgreden la ley viven un doble castigo. Por un lado por la transgresión a las normas penales y por otro por transgredir las normas de género y los roles sociales asumidos y asignados (Carlen, & Worrall, 2004).…”
Section: Los Aportes De Las Epistemologías Y Criminologías Feministasunclassified